2015
DOI: 10.1371/journal.pone.0125173
|View full text |Cite
|
Sign up to set email alerts
|

Transverse False Tendons in the Left Ventricular Cavity Are Associated with Early Repolarization

Abstract: BackgroundLeft ventricular false tendons (LVFTs) are related to precordial murmurs, ventricular arrhythmias and some repolarization abnormalities. Early repolarization (ER) is a specific type of repolarization abnormality.ObjectiveThe aim of the present study was to investigate the relationship between LVFTs and ER.MethodsThis study retrospectively included 99 consecutive healthy subjects and 33 patients with ER. Early repolarization was defined as an elevation of the QRS-ST junction of >0.1 mV from baseline i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
1
13
0
1
Order By: Relevance
“…This phenomenon is also seen in a study by Hall et al, where 15 out of 100 matched "controls" appeared to have an LVFT, supporting a more frequent prevalence of LVFTs in the general population [6]. An autopsy study by Luetmer et al described presence of LVFTs in 55% of hearts [7] and LVFTs were present in 78% and 83% of hospital-referred children and healthy subjects respectively [4]. The reported prevalence of LVFTs can also be subject to selection bias, as presence of LVFTs have been associated with innocent precordial murmurs.…”
Section: Prevalence Of Lvftsmentioning
confidence: 64%
See 1 more Smart Citation
“…This phenomenon is also seen in a study by Hall et al, where 15 out of 100 matched "controls" appeared to have an LVFT, supporting a more frequent prevalence of LVFTs in the general population [6]. An autopsy study by Luetmer et al described presence of LVFTs in 55% of hearts [7] and LVFTs were present in 78% and 83% of hospital-referred children and healthy subjects respectively [4]. The reported prevalence of LVFTs can also be subject to selection bias, as presence of LVFTs have been associated with innocent precordial murmurs.…”
Section: Prevalence Of Lvftsmentioning
confidence: 64%
“…Presence of LVFTs may be associated with abnormal ventricular repolarisation in young healthy subjects in competitive sports [4,[10][11][12]. Inverted symmetrical, sometimes biphasic, T waves can be seen (especially in V1-V3) which regress with increase in heart rate during exercise testing.…”
Section: Lvfts and Ecgmentioning
confidence: 99%
“…Nakagama et al found a frequent association in patients with type 1 and 2 false tendon and the presence of J waves (Nakagawa et al, 2012). Liu et al, 2015 also found a strong association between ER and the presence of false transverse tendon. On the other hand, the authors use the LA diameter to evaluate the dilatation of this chamber.…”
Section: Early Repolarization and Echocardiography: Some Aspects To Considermentioning
confidence: 92%
“…АРХ были впервые описаны в 1893 году W. A. Turner [5] и представляют собой тонкие образования, расположенные внутри сердца, которые не крепятся к створкам атриовентрикулярных клапанов, а прикрепляются к противоположным свободным стенкам желудочков или между папиллярными мышцами [6,7] и чаще всего они встречаются у мужчин [8]. Они могут обнаруживаться как самостоятельно, так и с другими малыми структурными аномалиями сердца, например -с ПМК [9].…”
Section: обоснование исследованияunclassified